Multidisciplinary approach to support the design of a local policy of payment for hydrological ecosystem services, in a microwatershed located in northern Veracruz, México - Chagoya Fuentes, Jorge L. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Ph.D.) - CATIE, Turrialba (Costa Rica), University of Bangor, 2009